Peracute Onset Pediatric Myelin Oligodendrocyte Glycoprotein Antibody Associated Focal Cortical Encephalitis: A Case Report - Pohl, Johanna Sophie; Leypoldt, Frank; Larsen, Naomi; Baalen, Andreas van; Wandinger, Klaus-Peter; Rostasy, Kevin; Muhle, Hiltrud (Archives of Clinical and Medical Case Reports, 2022)
Recently, several case series have described pediatric patients presenting with new onset focal seizures together with relapsing fever and cortical T2/FLAIR hyperintensities in association with myelin oligodendrocyte glycoprotein (MOG) antibodies, in adults known as unilateral cortical fluid-attenuated inversion recovery (FLAIR) hyperintense lesions in anti- MOG-associated encephalitis with seizures (FLAMES). A previously healthy 12-year-old girl first arrived to the emergency department with stroke-like symptoms, including hemiparesis, facial palsy, and severe headache. Heparin therapy was initiated; seizures were successfully treated with valproate. Due to persistent cortical edema in brain magnetic resonance imaging (MRI), anti-inflammatory treatment with high dose dexamethasone was initiated and led to prompt recovery. One month later, the patient displayed fever and headache of unknown origin. Brain MRI showed cortical FLAIR hyperintensities and leptomeningeal contrast enhancement. Cerebrospinal fluid (CSF) analyses including autoimmune diagnostics revealed a lymphocytic pleocytosis, elevated protein, and positive oligoclonal bands. MOG antibodies in serum and CSF were positive. Intravenous methylprednisolone (IVMP), followed by oral tapering, led to complete recovery, yet one relapse occurred and intravenous immunoglobulins (IVIG) were added, given monthly to date. Our patient remained relapse-free for eight months when moderate but persisting headache and paraesthesia reoccurred. Methylprednisolone therapy was given, but outstanding MOG antibodies in serum and CSF were negative. Therefore, maintenance therapy was not extended. Single focal seizures led to adjustment of antiseizure medication. In summary, this is the first case report of a pediatric patient with MOG encephalitis, first presenting stroke-like symptoms, rem